Hearing Things: Gloria Naylor’s 1996, Havana Syndrome, and the Acousmatic Fantasy - Nathaniel, Steven (Surveillance & Society, 2026)
In 1996, Gloria Naylor (2005) recounts a traumatic encounter with the surveillance state, one that begins with sonic harassment but ends with psychological instability. Uncertain what voices fill her mind, Naylor composes what she calls a fictionalized memoir, in which she projects the paranoia of surveillance onto the unstable medium of narrative voice. The indignity of “hearing things,” which features prominently in Naylor’s story, evokes a critical tradition that ranges from Eve Sedgwick’s (1997) theorization of paranoia to Joseph Masco and Lisa Wedeen’s (2024) more recent reimagination of “conspiracy/theory.” Although this interdisciplinary body of scholarship has established the indelibly literary demeanor of the surveilled life, it has yet to address hearing things as a fundamental problem of the digital world. As this essay argues, 1996 contests state surveillance not by reciprocating the data-collection process, but through fantasies of mystery voices and unverifiable—that is, acousmatic—sounds. The second section of this essay contends that increasingly ubiquitous and imperceptible surveillance technologies have made Naylor’s narrative strategy even more essential today. In 2016, American diplomats began to report hearing inexplicable noises as well as an array of neurological symptoms that news media have come to name Havana Syndrome. The diplomats’ government agencies largely dismissed their symptoms, and the experience of hearing things fell outside the procedures of clinical medicine, leading many to rehabilitate their minds through aesthetic means. This essay links the provocative narrative form of 1996 with the art therapies at Walter Reed Medical Center, before forecasting Naylor’s influence on the emerging counter-surveillant practices of the digital age.